2019
DOI: 10.33225/jbse/19.18.507
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Stem Activities Related to Work-Energy Topics on Academic Achievement and Prospective Teachers' Opinions on Stem Activities

Abstract: In this research, the effects of STEM (Science-Technology-Mathematics-Engineering) activities on academic achievement of prospective teachers were researched, their opinions on STEM activities were sought. The research was based on a semi-experimental model with pre-test and post-test control group. During the application phase, the topic of Work-Energy subject was taught through STEM based 5E model in the experimental group, while in the control group, the lessons were conducted using traditional teacher cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
2
8
0
3
Order By: Relevance
“…Research (Büyükdede & Tanel, 2019) proposed that an essential factor for countries to contemplate to improve their economy and become independent economically is the production of technology. Technology production is a multifaceted pursuit (Seck, 2015) and is initiated by encouraging and supporting students to pursue careers within Science, Technology, Mathematics and Engineering (STEM) related fields.…”
Section: Science Technology Mathematics and Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Research (Büyükdede & Tanel, 2019) proposed that an essential factor for countries to contemplate to improve their economy and become independent economically is the production of technology. Technology production is a multifaceted pursuit (Seck, 2015) and is initiated by encouraging and supporting students to pursue careers within Science, Technology, Mathematics and Engineering (STEM) related fields.…”
Section: Science Technology Mathematics and Engineeringmentioning
confidence: 99%
“…The ability to address challenges within the 4IR such as climate change, poverty, technology development, overpopulation and food security will depend on how enlightened society is in STEM-related subjects (Fadzil et al, 2019). For teachers of STEM-related subjects, knowledge of content is not the only requirement for developing well-qualified students as teachers ought to have the essential abilities to ensure effective teaching and learning of STEM-related subjects (Büyükdede & Tanel, 2019). Additionally, to be successful within the 4IR, a necessary approach for progression would be technology development (Seck, 2015).…”
Section: Fourth Industrial Revolutionmentioning
confidence: 99%
“…STEM education amalgamates the pedagogical content and abilities of Science, Technology, Engineering, and Mathematics (Schreffler et al, 2019). It offers the prospect for learners in strengthening their problem-solving skills, makes them innovators, creators, self-efficacious, technologically literate, communicator, critical thinkers, and problem-solvers (Büyükdede & Tanel 2019). Applications of STEM education makes students proficient with modern skills and gives birth to a scientific society (Margot & Kettler, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…STEM education focuses on the blend of skills and knowledge acquired in each STEM discipline (i.e., mathematics, technologies, informatics, biology, chemistry, physics, geography) into a science and technology educationoriented teaching (Büyükdede & Tanel, 2019). Researchers suggested that teachers find it difficult to approach STEM subjects interdisciplinarily (Kelley & Knowles, 2016, p. 1).…”
Section: Introductionmentioning
confidence: 99%